Evaluation of dimensional stability and tear strength: a preliminary study on polyvinyl siloxane impression material - Mohamad Firdaus Ahmad,; Nurul Izzah Rosli,; Ros Anita Omar,; Muhammad Aidil Roslan,; Noor Azlin Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigated the tear strength and dimensional stability of polyvinyl siloxane (PVS) impression materials following chemical disinfection and storage at various intervals. Aquasil Ultra+ was evaluated for dimensional stability, with 10 specimens fabricated according to American National Standards Institute/American Dental Association (ANSI/ ADA) Specification No. 19. After 1-h immersion in disinfectant, samples were sealed and stored for 24 h, 7 days, and 14 days. Dimensional changes were assessed using an image analyser at 20× magnification. Tear strength was tested in 12 specimens each of Aquasil Ultra+ and Chromaclone, prepared in accordance with American Society for Testing and Materials (ASTM) 1004 and evaluated using a universal testing machine at a crosshead speed of 51 mm/min. Statistical analysis included repeated measures analysis of variance and independent t-tests. The dimensional stability of Aquasil Ultra+ remained within the ADA’s 0.5% limit across all time points (p = 0.051). Tear strength differed significantly (p = 0.002), with Aquasil Ultra+ (7.48 ± 1.35 N/mm) outperforming Chromaclone (5.98 ± 0.70 N/mm). Both materials exceeded the minimum acceptable tear strength after 5 min of setting. Clinical implication: Aquasil Ultra+ offers clinicians reliable performance and flexibility in delayed model fabrication without compromising accuracy or material durability.